2014
DOI: 10.1007/s11999-013-3435-3
|View full text |Cite
|
Sign up to set email alerts
|

Reply to the Letter to the Editor: Advantages of Arthroscopic Transosseous Suture Repair of the Rotator Cuff without the Use of Anchors

Abstract: To the editor,We appreciate the valuable comments of Bicanic and colleagues, which describe previously reported transosseous suture methods, limitations, costs, possible pullout of the sutures, and complexities of the suturing in the procedure we reported.The hybrid technique of anchor and transosseous sutures reported by Cicak et al. [2], and the transosseous suture technique using a hollow needle reported by Matis et al.[5], differ from our technique. We make a long straight bone tunnel from the lower margin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…23,25 Equally important, the cost analysis performed by various authors has clearly shown the cost advantage of ATORCR versus arthroscopic anchor-based repair, even after taking into consideration the longer operative time. 3,17,25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,25 Equally important, the cost analysis performed by various authors has clearly shown the cost advantage of ATORCR versus arthroscopic anchor-based repair, even after taking into consideration the longer operative time. 3,17,25…”
Section: Discussionmentioning
confidence: 99%
“…23,25 Equally important, the cost analysis performed by various authors has clearly shown the cost advantage of ATORCR versus arthroscopic anchor-based repair, even after taking into consideration the longer operative time. 3,17,25 During ATORCR, the entry of the drill wire has been described by some authors in terms of its distance from the greater tuberosity. 8 The axillary nerve has been variously reported to lie about 35 to 53.5 mm from the tip of the greater tuberosity.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%
“…In 2013, we calculated the cost, including surgical time and personnel expenses, and found that our procedure is cheaper than the anchor method, unless the latter is completed within 6 minutes [18] . The only surgical material used is polyester thread and PGA thread.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the surgical cost between ATOS repair and the anchor method. 26 The difference in terms of cost according to surgical method is attributed to the use of surgical materials and professional fees. .…”
Section: Economic Advantage Of Atos Repairmentioning
confidence: 99%